Enhancement of germination performance and early seedling growth of Malaysian indica rice (Oryza sativa L.) cv. MR219 by hormonal priming - Sukifto, Mohamad Rasyid (2020)
Seed germination and early seedling establishment is a critical stage of rice life cycle that determines its survival and productivity. The success of germination and seedling establishment is affected by both abiotic and biotic factors and the seed physiological attributes. Enhancing seed quality for direct seeding method of rice cultivation by priming under unfavourable conditions is commonly practised. However, improving poor germination and seedling establishment of Malaysia's indica rice (Oryza sativa L.) MR219 under normal growth condition by priming has yet to be conducted. Therefore, this study aimed to increase germination performance and early seedling growth of MR219 rice cultivar by determining the optimum priming time and ideal concentration of hormones under normal growth conditions. MR219 seeds were primed with salicylic acid (SA) and gibberellic acid (GAJ) in ranges of concentrations (20-100 mg L-1) for 12 and 18 hours separately. Unprimed seed was used as control. Germination was conducted using completely randomized design (CRD) with four replicates for eight cycles and seeds were allowed to germinate for ten days at room temperature (25±1 °C). MR219 seeds were also primed with combination of SA+GAJ at 12 hours. Following this, cultivation of primed MR219 seed was carried out in the pots in the field conditions using randomised complete block design (RCBD) with 8 replicates for 4 weeks. Germination and early seedling growth parameters were measured and statistically analysed using Analysis of Variance (ANOVA) at p<0.05 followed by Duncan Multiple Range Test (DMRT) at p<0.05 for mean comparison. Results showed 12 hours hormonal priming with SA and GA3 between 60-100 mg L-1 enhanced germination performance and early seedling growth of MR219 with germination percentage achieved 80-100%, germination index increased 2-fold, seed vigour increased 3-fold, coefficient of velocity of germination increased exceeding 2%, 100% increase in seedling height and reduced the mean germination time by 24 hours. Germination performance of MR219 seeds primed with GAJ showed the best germination performance compared to unprimed seed. However, experiment using a combination of SA+GA3 priming showed reduction in germination performance and early seedling growth compared to single priming. Contrarily, cultivation of primed MR219 seeds in pots showed better establishment and early seedling growth under SA priming at 12 hours, exhibiting better morpho-physiological characteristics with seedling height increased a 2-fold and total fresh weight a 3-fold accompanied by increased in cell membrane integrity compared to unprimed seedlings. In addition, SA priming significantly improved the biochemical properties of MR219 seedlings with increased in carbohydrate content, protein content and 4-fold in total soluble sugar compared to unprimed seedling. As a conclusion, hormonal priming with SA (100 mg L-1) at 12 hours determined to be the best priming method to enhance germination performance and early seedling growth of MR219 rice cultivar.